2019
DOI: 10.3390/su11092540
|View full text |Cite
|
Sign up to set email alerts
|

Regions’ Technology Brokerage Patterns and Dynamics for Regional Development

Abstract: While extant studies on brokerage address its structural competitiveness and network performance, few studies address the fundamental question of whether all the brokerage types have identical and positive effects on network development. Extending the Gould and Fernandez’s brokerage topology, the study measures the contribution of the brokerage roles over to the network evolution. For the purpose, the Chinese technology transfer flow networks were utilized to reveal the brokerage patterns of three anchor regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…While brokerage is becoming a more prevalent concept in this literature, only a few papers investigate the varying effect of different brokerage types. Drawing on the need to understand the heterogeneity of brokers, Seo [ 45 ] examines what kind of technology broker is needed for economic development; Sigler et al [ 46 ] look at city-regions in the context of global corporate networks, and by using the GF brokerage measure find that city-regions confer economic advantage through their brokerage roles. Martinus et al [ 47 ] investigate how small states and territories act as brokers in the global corporate network.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While brokerage is becoming a more prevalent concept in this literature, only a few papers investigate the varying effect of different brokerage types. Drawing on the need to understand the heterogeneity of brokers, Seo [ 45 ] examines what kind of technology broker is needed for economic development; Sigler et al [ 46 ] look at city-regions in the context of global corporate networks, and by using the GF brokerage measure find that city-regions confer economic advantage through their brokerage roles. Martinus et al [ 47 ] investigate how small states and territories act as brokers in the global corporate network.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Gould 等 [12] 的研究, [31] 。这些企 业早期已经与获取知识的区域外主体建立了稳定 且可以信赖的联系, 长期的合作可以降低交易成本 且增加双向学习的机会 [32] [33] 。需要指出的是, 一些企业尤其是浙江省 的宁波市、 绍兴市和台州市的企业由单纯的知识 "接收者" 转变为新知识的 "创造者" 和向其他主体 外部主体的互动 [34] 。 "开放科学" 推动了大学科研范 式的根本转型, 大学开始从传统的学术 "象牙塔" 向 守门人的组织角色转型 [6] 溢出; Jacobs [37] 论证了集聚经济对于创新活动非常 重要, 多样化的环境易于知识传递。因此为考虑到 集聚带来的知识外部性, 选取 2 个变量用以衡量创 新投入的规模与集聚经济的相关性: 第一个变量 NP 为城市在时间 t 的内部专利即排除包括城市外 部发明人的专利数量。Kogler 等 [38] 认为该数值可以 反映城市层面创新的规模效应以及知识扩张的潜 力。第二个变量为创新主体的赫芬达尔-赫希曼 指数(HHIm), 具体公式为:…”
Section: 识与资源。由于外部联系的重要性随着节点之间unclassified
“…The results showed that inter-city transfer of technology was increasingly higher frequency, and the network presented a core radiation pattern. Seo [40] used China's technology transfer stream network to reveal brokering models in three major regions: Beijing, Shanghai, and Shenzhen. They found that Beijing and Shenzhen tend to transfer technology as a national hub in the national innovation system, rather than as a local hub in large cities.…”
Section: Literature Reviewmentioning
confidence: 99%